2018
DOI: 10.1063/1.5016305
|View full text |Cite
|
Sign up to set email alerts
|

Mode decomposition and Lagrangian structures of the flow dynamics in orbitally shaken bioreactors

Abstract: In this study, two mode decomposition techniques were applied and compared to assess the flow dynamics in an orbital shaken bioreactor (OSB) of cylindrical geometry and flat bottom: proper orthogonal decomposition and dynamic mode decomposition. Particle Image Velocimetry (PIV) experiments were carried out for different operating conditions including fluid height, h, and shaker rotational speed, N. A detailed flow analysis is provided for conditions when the fluid and vessel motions are in-phase (Fr = 0.23) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 35 publications
1
12
0
Order By: Relevance
“…In that regime the liquid distribution at the tank wall is in opposition to the inertial forces. That phenomenon is also well known from orbitally shaken bioreactors, where the phase shift was found to significantly influence the flow fields and the mixing of the flow (Weheliye et al 2018). This predicted phase shift could be verified by different experiments in the regions sufficiently far away from the resonance frequency.…”
Section: Realization Of Phase-shift Measurements Using a Reference Desupporting
confidence: 77%
See 1 more Smart Citation
“…In that regime the liquid distribution at the tank wall is in opposition to the inertial forces. That phenomenon is also well known from orbitally shaken bioreactors, where the phase shift was found to significantly influence the flow fields and the mixing of the flow (Weheliye et al 2018). This predicted phase shift could be verified by different experiments in the regions sufficiently far away from the resonance frequency.…”
Section: Realization Of Phase-shift Measurements Using a Reference Desupporting
confidence: 77%
“…These bioreactors are of particular interest for fluid dynamists since they offer a high potential for optimization in terms of mixing efficiency and power consumption. Various properties as the influence of different characterized wave and flow regimes to the mixing efficiency, the mass transport or shear stress distributions were numerically and experimentally studied by Weheliye et al (2012); Ducci and Weheliye (2014); Reclari et al (2014); Bouvard et al (2017); Weheliye et al (2018); Alpresa et al (2018a,b). Some of their findings can be directly transferred to interfacial wave systems, as we will discuss in Sect.…”
Section: Introductionmentioning
confidence: 99%
“…The POD capability to extract coherent structures, which exhibit patterns in space and also in time, is particularly relevant in mixers, because these structures are the basis of the mixing mechanisms: folding and stretching of fluid elements [7,8] . POD has been applied to chemical engineering in the analysis of stirred tanks [9][10][11][12] and recently orbitally shaken reactors [13] .…”
Section: Introductionmentioning
confidence: 99%
“…Due to the prevalence of STRs in the chemical and biochemical industries, several studies can be found in the literature that provide a thorough investigation of their mixing and fluid dynamics characteristics for a broad range of operating conditions [1, 2,3,4,5,6]. In recent years, the engineering characterisations of labscale OSRs have also been conducted by various researchers in terms of flow dynamics [7,8,9,10,11,12], free surface motion [13,14], solids suspension [15,16] and power consumption [17,18,19], both experimentally and numerically.…”
Section: Introductionmentioning
confidence: 99%